SPEECH ABNORMALITY OF THE SCHIZOPHRENIC MAIN CHARACTER IN FRACTURED MOVIE - Rosabila Hardi Irfandina; Rohmani Nur Indah (CALL, 2022)
One major difficulty of a person with schizophrenia is the ability to communicate and express his or her thought just like the common people due to several symptoms, such as hallucinations and delusions. It may result in various type of speech abnormalities. This study aims to present a comprehensive description on the types of speech abnormality of the schizophrenic main character in Fractured movie. It is based on the assumption that Ray Monroe as the main character has represented the schizophrenic speech abnormalities. Employing a descriptive qualitative research design, this study took the data from Ray Monroe's utterances transcribed from the movie, then analyzed them using the framework of Liddle et al. and Covintong et al. to describe how the speech abnormality appears. The findings indicated that of the schizophrenic's utterances cover eight types of speech abnormality. These included weakening of the purpose, looseness, strange logic, strange sentences, concept preservation, and distractibility. The positive and negative symptoms of schizophrenia, which have an impact on thought, language, and emotion, are the two main symptoms that create the speech abnormalities. When Ray Monroe made a claim using illogical language and without supporting evidence based on reality and developed odd logic. Keywords: psycholinguistics, schizophrenia, speech abnormality